Character Analysis Analysis of Deconstruction on the Character of Kiran in ‘Tuhan Izinkan Aku Menjadi Pelacur!’ Novel by Muhidin M Dahlan - Deny Tri Aryanti (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2022)
This study aims to describe the deconstruction form of Kiran’s life, the main character in the ‘Tuhan Izinkan Aku Menjadi Pelacur!’ novel, by Muhidin M Dahlan. In this study, the novel itself served as the source of data and it was analyzed by using Jacques Derrida’s deconstruction method. This study shows how the main character's desire to struggle against a religious culture is being deconstructed. She ultimately carried out the destruction and rebellion in the construction that he had previously accepted and solemnly believed in because of the disappointment felt by God and men. A reversal situation of someone who was once quite religious, to someone who no longer obeys his religion and God. She even disregarding His teachings and eventually losing faith in God's power. There are attempts to shake, break, and destroy Kiran's resistance in this instance.